2011
DOI: 10.1177/1049732311413907
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Processes at a Camp for Youth With HIV/AIDS

Abstract: The impact of HIV/AIDS on the lives of youth with this chronic illness suggests the need for additional support as youth develop. Summer camp can serve as a therapeutic intervention for youth with HIV/AIDS. Using a case study employing observations, focus groups, and interviews, we examined outcomes associated with participation in a camp for youth with HIV/AIDS, and program processes that influenced outcomes. Findings showed that camp played a major developmental role for youth. Three outcomes of camp emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(114 citation statements)
references
References 76 publications
3
102
0
9
Order By: Relevance
“…Exposure to "similar others" is a camp feature that normalizes one's experience (Gillard & Watts, 2013, p. 895). As Gillard et al (2011) have noted, the unstructured and informal interactions that are built into the camp setting provide an ideal environment for developing positive relationships. Parents perceived significant increases in self-efficacy for their campers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to "similar others" is a camp feature that normalizes one's experience (Gillard & Watts, 2013, p. 895). As Gillard et al (2011) have noted, the unstructured and informal interactions that are built into the camp setting provide an ideal environment for developing positive relationships. Parents perceived significant increases in self-efficacy for their campers.…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains reports of using the camp setting as a means to bring together those with the same chronic illnesses and health conditions, such as cancer (Conrad, & Altmaier, 2009;Gillard & Watts, 2013;Martiniuk, 2003), HIV/AIDS (Gillard, Witt, & Watts, 2011), and spina bifida (Holbein et al, 2013), among others, and with shared life circumstances such as bereavement (Creed, Ruffin, & Ward, 2001;Nabors et al, 2004). A systematic review of 21 studies of camps for children with chronic illnesses showed a high level of satisfaction and improvements in social-related outcomes, but noted some methodological limitations (Moola, Faulkner, White, & Kirsh, 2013).…”
Section: Camp As a Setting For Positive Youth Developmentmentioning
confidence: 99%
“…Camps are the closest example, and some qualitative studies from camps exist in the literature. Camps for young people living with HIV/AIDS offer settings for young people to access information about their condition and build a sense of community with peers (Gillard et al, 2011). However, camp curricula concentrate on recreational activities, designating just a fraction of the program to structured conversations about living with HIV/AIDS (Gillard et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As affirmed by Gillard, Witt, and Watts (2011) and Hrenko (2005), the body of literature on HIV camps is extremely scant. As such, the literature review was then widened to include non-camp recreation programming, focusing on impacts and benefits derived from the programming that would also be applicable to a camp setting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gillard et al (2011) undertook a study of a recreational camp program for youth with HIV in the Southern United States, noting the relevance of "nonclinical therapeutic intervention outside the formal medical setting" -and the lack of nonmedical research on this subject (p. 1508). The authors found that this camp experience addressed several challenges faced specifically by youth with HIV, such as dilemmas around disclosure, and problems linked to the demographics associated with HIV, such as poverty, parental drug use, and change in primary caregivers.…”
Section: Hiv-specific Campsmentioning
confidence: 99%